The Paradox of Negative Antibody Screening and Positive Crossmatching: Implications for Transfusion Safety in a Developing Country - Suryanto; Adang Muhammad Gugun (Open Access Indonesian Journal of Medical Reviews, 2025)
Modern antibody screening is a pillar of transfusion safety, intended to prevent hemolytic reactions. However, its ultimate effectiveness, particularly in diverse populations within developing nations where abbreviated crossmatch protocols are not feasible, remains a critical question. This study investigates the "safety gap" between negative screening results and final patient-donor compatibility, aiming to quantify the incidence of serological incompatibility detected by mandatory crossmatching in a tertiary hospital in Indonesia. A descriptive, cross-sectional study was conducted from March to June 2024 at the Blood Bank of PKU Muhammadiyah Yogyakarta Hospital. A total of 299 donor-recipient pairs were analyzed via total sampling. Donor units were screened for irregular antibodies using an automated Column Agglutination Technology (Gel Test) with comprehensive three-cell panels. Subsequently, major and minor crossmatches for all pairs were performed using a Gel Test-based Indirect Antiglobulin Test (IAT) incubated for 15 minutes at 37°C. All 299 donor samples (100%) yielded negative results for irregular antibodies during screening. However, the final crossmatch revealed serological incompatibilities. Major crossmatching (patient serum vs. donor cells) identified incompatibility in 4 cases (1.34%). Minor crossmatching (donor serum vs. patient cells) showed a significantly higher rate of incompatibility, found in 21 cases (7.03%). The predominant blood component transfused was Packed Red Cells (91.97%). In conclusion, the findings demonstrate a significant paradox where a substantial rate of serological incompatibility is only detected by the final crossmatch. This study quantitatively confirms that antibody screening alone is insufficient to guarantee blood compatibility. These results challenge the safety of adopting abbreviated crossmatch protocols in this setting and affirm that the physical crossmatch remains an indispensable, non-negotiable safeguard. This provides critical, region-specific evidence for strengthening hemovigilance systems and reinforcing transfusion policies in Indonesia and other resource-limited nations.